2020
DOI: 10.3390/rs12152458
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Peat Thickness Using a Multi-Receiver Electromagnetic Induction Instrument

Abstract: Peatlands constitute extremely valuable areas because of their ability to store large amounts of soil organic carbon (SOC). Investigating different key peat soil properties, such as the extent, thickness (or depth to mineral soil) and bulk density, is highly relevant for the precise calculation of the amount of stored SOC at the field scale. However, conventional peat coring surveys are both labor-intensive and time-consuming, and indirect mapping methods based on proximal sensors appear as a powerful suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…These findings agree with the recent work of Beucher et al. (2020) who found that the best approach for determining peat thickness was using a linear regression method and that it performed better than inverse models obtained from using the Aarhus workbench (Auken et al., 2009). Moreover, given that at low conductivity values the ERT calibration is assumed linear, bypassing the ERT calibration of the EMI data does not substantially reduce the performance of the multi‐linear regression prediction method.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These findings agree with the recent work of Beucher et al. (2020) who found that the best approach for determining peat thickness was using a linear regression method and that it performed better than inverse models obtained from using the Aarhus workbench (Auken et al., 2009). Moreover, given that at low conductivity values the ERT calibration is assumed linear, bypassing the ERT calibration of the EMI data does not substantially reduce the performance of the multi‐linear regression prediction method.…”
Section: Discussionsupporting
confidence: 92%
“…However, recently the usage of frequency-domain electromagnetic induction (EMI) methods for wetland characterization has increased; this is in part due to the ease at which relatively large areas can be surveyed (e.g. von Hebel et al, 2014;Rejiba et al, 2018;Beucher et al, 2020). Furthermore, although the work here focusses on EMI methods it is worth noting that other geophysical methods have been employed successfully in similar wetland environments, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Portable electromagnetic induction (EMI) sensors using harmonic source waveforms (also known as frequency-domain electromagnetics -FDEM) are commonly used to characterize near-surface geoelectrical properties. Such methods are used in various applications including archaeological prospection (De Smedt 5 et al, 2014;Dabas et al, 2016;von Hebel et al, 2021), precision agriculture (Jadoon et al, 2015;Rudolph et al, 2016;Brogi et al, 2019), hydrological studies (Vereecken et al, 2015;von Hebel et al, 2014;Rezaei et al, 2016;Robinet et al, 2018), and environmental studies including the exploration of peat deposits (Altdorff et al, 2016;Beucher et al, 2020;Clément et al, 2020;10 McLachlan et al, 2020). Modern single-frequency, multi-configuration sensors can simultaneously sense the subsurface electrical conductivity for different volumes of investigation.…”
Section: Introductionmentioning
confidence: 99%